Steady MHD Flow of Nano-Fluids over a Rotating Porous Disk in the Presence of Heat Generation/Absorption: a Numerical Study using PSO - Z. Uddin; R. Asthana; M. K. Awasthi; S. Gupta (Journal of Applied Fluid Mechanics, 2017)
In this paper, a numerical integration technique, based on particle swarm optimization is proposed to investigate the effects of internal heat generation/absorption, on MHD boundary-layer flow of different types of nano-fluids over a rotating disk with uniform suction. Thermo-physical properties are modeled based on a wide range of experimental data. In the model, effect of nature of base fluid, nature of nano-particle material, size of nano particle, concentration of nanoparticle in the base fluid, nano-thermal layer formed around the nano particle etc. are taken into consideration. The two dimensional non-linear partial differential equations governing the flow are reduced to a system of coupled non-linear ordinary differential equations by using similarity transformations. These non-linear equations have been solved by using shooting based integration technique along with particle swarm optimization. In this study, four different types of water bases nanofluids are compared with respect to heat transfer enhancement, and the effects of nano-particle concentration, nano-particle size and heat generation/absorption parameters are studied in detail. The effects of different parameters on the dimensionless velocity profile and temperature distribution are discussed graphically. It is found that out of the four nano fluids considered, the heat transfer rate for CuO water based nano fluid is highest. It is also concluded that small sized nano-particles, high suction and high heat absorption increase the heat transfer rate.